Preparation method and application of oleogel based on protein fibers

By using protein fiber-barley-glycin-xanthan gum composite gel agent to prepare oil gel, the problems of saturated fatty acids and trans fatty acids in existing solid oils are solved, and oil gels with uniform texture, stable structure and high oil resistance are obtained, which are suitable for food processing and other fields.

CN119563720AActive Publication Date: 2025-03-07CHINA AGRI UNIV

Patent Information

Application Number
CN202510138411.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-07
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

Existing solid oils contain more saturated fatty acids and trans fatty acids. Excessive intake will increase the risk of cardiovascular and cerebrovascular diseases. The safety issues of small-molecular gels and the heating preparation process may lead to deterioration of oils, limiting their application. Oil gels prepared from single protein or polysaccharides have problems such as uneven texture, poor structural stability and low oil retention.

Method used

Oil gels were prepared by the emulsion template method using the protein fiber-barium-xanthan gum composite gel agent. Oil gels with uniform texture, stable structure and high oil strength were obtained through the steps of cereal alkaloid extraction, protein fiber preparation and oil gel preparation.

Benefits of technology

The prepared oil gel has a smooth surface, a soft texture, good adhesiveness and temperature stability, high oil resistance, and is suitable for food processing and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119563720A_ABST
    Figure CN119563720A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of food engineering and the field of biological macromolecular materials, and particularly relates to a preparation method and application of oleogel based on protein fibers. The oleogel is prepared from the prolamin from barley and different protein fiber and xanthan gum compounds, the obtained oleogel has high oil holding capacity, high storage modulus, better thixotropic resilience and good temperature and thermodynamic stability, and different types of oleogels can be suitable for different processing scenes, so that the oleogel can be applied to different processing fields. The method can be widely applied to the fields of foods, medicines and cosmetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials and food science and technology, and specifically relates to a preparation method and application of protein fiber oil gel. Background Art

[0002] Solid oils and fats are widely used in food processing because they can give food a certain flavor, texture and taste. Traditional solid oils and fats are mainly refined animal fats or partially hydrogenated vegetable oils. However, these solid oils and fats contain more saturated fatty acids, especially hydrogenated vegetable oils, which contain a certain amount of trans fatty acids. Excessive intake will increase the risk of cardiovascular and cerebrovascular diseases.

[0003] Oleogel is an effective fat substitute that converts liquid oil into a solid form by forming a three-dimensional network structure through a gelling agent. Oleogel can be prepared by directly heating and mixing small molecule gelling agents (such as beeswax, glyceryl monostearate, etc.) and then cooling. However, the safety of gelling agents is controversial, and the heating process may cause oil deterioration, which limits the wide application of small molecule gelling agents. Biomacromolecules (such as proteins and polysaccharides) are widely accepted due to their good biocompatibility, safety and non-toxicity, and can be prepared by indirect methods. However, oleogels prepared using single proteins or polysaccharides have defects such as uneven texture, poor structural stability, and low oil holding capacity, which limits their application in actual production and processing. Therefore, protein fiber-hordein-xanthan gum composite gelling agent is used to prepare oleogels to obtain oleogels with uniform texture, stable structure and high oil holding capacity.

[0004] Solid oils commonly used in modern processing often contain more saturated fatty acids and trans fats, and a large amount of intake will increase the risk of suffering from cardiovascular and cerebrovascular diseases. Oil gel is an effective substitute. However, small molecule gels are widely used in food processing due to safety issues and the problem of oil quality degradation that may be caused by the heating preparation process. The oil gel prepared by a single biomacromolecule (such as protein, polysaccharide) still has deficiencies in terms of texture, structural stability, oil holding capacity, etc. Therefore, the present invention adopts composite biomacromolecules (protein fiber-hordein-xanthan gum) as oil gel, and the prepared oil gel is improved in terms of texture, stability, oil holding capacity, etc., and has processing application prospects. Summary of the invention

[0005] In order to overcome the above-mentioned defects of the prior art, the present invention provides the following technical solutions, specifically: The first aspect of the present invention is to provide a method for preparing an oil gel based on prolamin, the method comprising the following steps: 1) Extraction of cereal alcohol-soluble protein: The shelled cereal kernels are crushed into powder using a high-speed grinder, and after defatting, washing with water and salt, the protein is extracted using 75% ethanol, and the extract is freeze-dried to obtain cereal alcohol-soluble protein powder; 2) Preparation of fibers: Prepare the protein aqueous solution with deionized water, heat it under acidic conditions, and obtain the stock solution of each protein fiber after cooling; 3) Preparation of oil gel: The oil gel was prepared by an emulsion template method, wherein the grain alcohol-soluble protein obtained in step 1) was dissolved in 75% ethanol to prepare a grain alcohol-soluble protein solution, which was then added to the protein fiber solution prepared by the protein fiber stock solution prepared in step 2) under stirring, and then xanthan gum powder was added to the above solution respectively; 4) adding an equal volume of vegetable oil to prepare an oil-in-water emulsion; 5) The emulsion obtained above is freeze-dried to obtain the corresponding oil gel.

[0006] Furthermore, the cereals in step 1) include but are not limited to barley, oats, wheat, rye, and corn; preferably barley and oats; most preferably barley.

[0007] Furthermore, the protein described in step 2) includes but is not limited to whey protein isolate, egg white protein, soy protein isolate, and pea protein isolate.

[0008] Furthermore, the concentration of the cereal alcohol-soluble protein solution in step 3) is 5-15 mg / mL, preferably 8-12 mg / mL, and most preferably 10 mg / mL.

[0009] Furthermore, in step 3), the concentration of the protein fiber solution is 5-15 mg / mL, preferably 8-12 mg / mL, and most preferably 10 mg / mL.

[0010] Furthermore, the volume ratio of the cereal alcohol-soluble protein solution to the protein fiber solution in step 3) is 1:1.5-3, preferably 1:1.8-2.5, and most preferably 1:2.

[0011] Furthermore, the stirring speed in step 3) is 300-800 rpm, preferably 400-600 rpm, and most preferably 500 rpm.

[0012] Furthermore, in step 3), the final concentration of xanthan gum is 1-4 mg / mL, preferably 2-3 mg / mL, and most preferably 2.5 mg / mL.

[0013] Furthermore, the vegetable oil added in step 4) includes but is not limited to soybean oil, corn oil, and peanut oil, preferably soybean oil.

[0014] Furthermore, in step 4), the volume of the vegetable oil added is 0.8 to 1.2 times of the solution obtained in step 3), preferably the same volume, so as to obtain an oil-in-water emulsion with an oil phase volume fraction of 50%.

[0015] The second aspect of the present invention is to provide an oil gel prepared by the method described in the first aspect.

[0016] The third aspect of the present invention is to provide the use of the oil gel described in the second aspect in food processing.

[0017] Furthermore, the applications include but are not limited to being used as a food ingredient or processing aid, as a carrier matrix, and as a substitute for trans fatty acids.

[0018] The fourth aspect of the present invention is to provide the use of the oil gel described in the second aspect in the pharmaceutical field.

[0019] Furthermore, the applications include but are not limited to being used as a drug carrier and as a nutritional supplement.

[0020] The fifth aspect of the present invention is to provide application of the oil gel described in the second aspect in the field of cosmetics.

[0021] Furthermore, the applications include but are not limited to bases for sunscreens and skin care products.

[0022] The beneficial effects of the present invention include: 1) The oil gel obtained by the method of the present invention has a smooth surface, a soft texture, good adhesiveness, does not flow after the container is inverted, and can maintain a certain shape autonomously.

[0023] 2) Oil gels all have high oil holding capacity.

[0024] 3) The oil gels all have high storage modulus (G'), elasticity is dominant, and they have good thixotropic resilience. In the range of 25-80℃, G'>G", they still show solid-like properties and good temperature stability.

[0025] 4) Oil gel has good viscosity and elasticity, and different types of oil gel can be suitable for different processing scenarios.

[0026] 5) The oil gel has a thermodynamic stability similar to that of soybean oil and is suitable for daily cooking. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 the hydrophobicity of the proprotein and its corresponding fibers; Figure 2 Transmission electron microscopy of protein fibers (A), fiber-hordein complex (B), hordein, xanthan gum and their complex (C), and fiber-xanthan gum complex (D); Figure 3 Oil gel appearance (A, B, C) and oil holding capacity (D); Figure 4 Oil gel strain sweep (A), frequency sweep (B), viscosity sweep (C), thixotropy test (D), and temperature sweep (E); Figure 5 DSC curves of oil gel. Heating (A) and cooling (B). DETAILED DESCRIPTION

[0028] The following is a further description of the concept of the present invention and the technical effects produced in conjunction with specific embodiments, so as to fully understand the purpose, features and effects of the present invention. The methods are conventional methods unless otherwise specified. The materials can be obtained from public commercial channels unless otherwise specified. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0029] Example 1 Preparation and property identification of protein fiber oil gel 1. Protein fiber preparation 1) Hordeoyl alcohol protein extraction: The shelled barley kernels were ground into powder using a high-speed grinder. The barley flour and n-hexane were soaked at room temperature in a mass ratio of 1:5 for 1 h. The precipitate was centrifuged at 4000 rpm for 5 min and washed with ultrapure water and 0.1 mol / L sodium chloride solution in a mass ratio of 1:5, respectively, and centrifuged under the same conditions as above. The precipitate after centrifugation was added with 75% ethanol solution in a mass ratio of 1:10, and protein was extracted for 2 h at room temperature under magnetic stirring. The supernatant was centrifuged at 4000 rpm for 5 min, and the ethanol was evaporated by rotary evaporation at 45°C. The lyophilized protein powder was obtained by freeze-drying at -80°C for 48 h.

[0030] 2) Preparation of fibers: whey protein isolate fiber (WPIF) and ovalbumin fiber (OVAF): whey protein isolate (WPI) powder and ovalbumin (OVA) powder were dissolved in deionized water to prepare a 10 mg / mL solution, which was fully hydrated at 4°C overnight. The pH was then adjusted to 2.0, and the solutions were heated in a water bath at 85°C for 24 h and immediately cooled in an ice water bath to form WPIF and OVAF stock solutions, which were stored at 4°C.

[0031] Soy protein isolate fiber (SPIF): Dissolve soy protein isolate powder (SPI) in deionized water to prepare a 10 mg / mL solution, fully hydrate at 4°C overnight, then adjust the pH to 2.0, add NaCl to adjust the ionic strength to 0.1 M, heat in a water bath at 85°C for 8 h, and incubate at room temperature for 3 days to form a SPIF stock solution, which is stored at 4°C.

[0032] Pea protein isolate fiber (PPIF): Dissolve pea protein isolate (PPI) in deionized water to prepare a 40 mg / mL solution, incubate at 4°C overnight for full hydration, centrifuge at 4000 rpm for 5 min, take the supernatant (concentration of about 16 mg / mL), adjust the pH to 2.0, heat in a water bath at 85°C for 24 h, and immediately cool in an ice water bath to form a PPIF stock solution and store at 4°C.

[0033] 3) Preparation of oil gel: The oil gel was prepared by emulsion template method. The barley alcohol-soluble protein solution (10 mg / mL, dissolved in 75% ethanol aqueous solution) was added to the 10 mg / mL WPIF, OVAF, SPIF and PPIF solutions prepared above at a volume ratio of 1:2 and a stirring speed of 500 rpm. Then, the xanthan gum powder was added to the above solutions to make the final concentration of xanthan gum 2.5 mg / mL. Then, an equal volume of soybean oil was added and homogenized at 9000 rpm for 40 s using a high-speed homogenizer (PhD Technology LLC, USA) to obtain an oil-in-water emulsion with an oil phase volume fraction of 50%. The above four emulsions were freeze-dried at -80°C for 48 h to obtain the corresponding oil gels. The complexes of WPIF-hordein, OVAF-hordein, SPIF-hordein and PPIF-hordein were named WH, OH, SH and PH, respectively. The complexes of WPIF-hordein-xanthan gum, OVAF-hordein-xanthan gum, SPIF-hordein-xanthan gum and PPIF-hordein-xanthan gum were named WHX, OHX, SHX and PHX, respectively. In addition, the emulsions prepared from WHX, OHX, SHX and PHX were marked as WHXE, OHXE, SHXE and PHXE, respectively, and the corresponding oil gels were named WHXO, OHXO, SHXO and PHXO, respectively.

[0034] 2. The surface hydrophobicity (H0) of the original protein and its corresponding fiber was measured.

[0035] 1) Dilute the sample in a gradient from 0.02 to 0.10 mg / mL with deionized water (pH 3.0).

[0036] 2) Subsequently, each sample solution was mixed with 10 μL of ANS (1-anilino-8-naphthalenesulfonate) solution (8 mmol L -1 , dissolved in 10 mM PBS) and mixed.

[0037] 3) After incubation in the dark for 10 min, the fluorescence intensity of the sample at an excitation wavelength of 390 nm and an emission wavelength of 470 nm was measured using a fluorescence spectrophotometer (Cary Eclipse, Agilent Technologies Inc, USA). The slope of the fluorescence intensity versus concentration is represented by H0.

[0038] like Figure 1 As shown in the figure, the unfibrillated protein raw materials are mixtures that have been extracted and purified and have different hydrophobicities. Among them, WPI and OVA are animal proteins that originally exist in a polar water environment (whey or egg white) and have low hydrophobicity. SPI contains 40-50% 11S globulin and has a higher hydrophobicity. PPI soluble protein accounts for about 40% and has the lowest hydrophobicity. The hydrophobicity of different protein raw materials increases after fibrillation. The reason may be that the fibrillation process will cause the protein to unfold and deconstruct, and reorganize to form a zipper-like structure of more hydrophobic β-pleated sheets. According to the level of hydrophobicity, we can divide the fibers into three groups: SPIF (high hydrophobicity), WPIF and OVAF (medium hydrophobicity) and PPIF (low hydrophobicity).

[0039] 3. Morphology of different fibers and their composites The morphology of the fibers and their composites was characterized by transmission electron microscopy (JEM 1200EX, JEOL, Japan) at 100 kV. 10 μL of the diluted sample was dropped on a copper grid and allowed to stand for 10 min, then washed with deionized water and negatively stained with uranyl acetate solution. The excess solution was removed with filter paper before observation.

[0040] Figure 2 A shows the morphology of WPIF, OVAF, SPIF, and PPIF, which are respectively long strips (diameter less than 10 nm, length up to micrometer level), short rods (diameter less than 10 nm, length less than 200 nm), beads (diameter up to tens of nanometers, length up to micrometer level), and worms (diameter less than 10 nm, length greater than 200 nm). Figure 2 C shows the morphology of hordein, whose particle size distribution is uneven, with an average value of about 200 nm. Figure 2B shows the binding of different protein fibers to hordein. The addition of hordein leads to the formation of a cross-linked network of fibers, which is located in the cross-linked part of the fiber network in a granular form (indicated by red arrows). This phenomenon may be due to the spontaneous binding of the hydrophobic groups of the protein molecules with the hydrophobic groups of the fibrils when introduced into a highly polar environment. OVAF is softer and shorter than WPIF, and cross-links with hordein to form a denser network. However, for SPIF, hordein tends to coat the surface of SPIF, inhibiting the cross-linking and extension of the network. This may be due to the high hydrophobicity of SPIF providing more binding sites for hordein. In contrast, PPIF has a long and soft nature and tends to self-entangle (indicated by blue circles), and hordein also tends to self-aggregate into larger particles (indicated by red circles).

[0041] To explore the combination of xanthan gum with other ingredients, we observed the morphologies of xanthan gum, fiber-xanthan gum, and hordein-xanthan gum. Figure 2 As shown in C, single xanthan gum exists in the form of spherical nanoparticles (about 20 nm in diameter) and filamentous structures. The shape and size of the hordein-xanthan gum complex are similar to those of hordein, and xanthan gum is encapsulated on the surface of hordein in the form of nanoparticles. Figure 2 As shown in Figure D, the addition of xanthan gum did not change the original shapes of WPIF, OVAF, and SPIF, but attached to the fiber surface in the form of small particles. In contrast, PPIF tended to be self-entangled and coated by xanthan gum nanoparticles.

[0042] 4. Appearance and Oil Holding Capacity (OBC) of Oil Gel The appearance of the oil gel was photographed with a digital camera. OBC was determined by centrifugation: 1.0 g of oil gel was placed in a 1.5 mL test tube, centrifuged at 4000 × g, 25°C for 20 min, and the test tube was inverted on filter paper for 10 min to remove free oil. OBC was calculated by the following formula: OBC (%) = m / m0 × 100 (1) Where m is the mass of the residual oil gel after centrifugation, and m0 is the mass of the initial oil gel.

[0043] Figure 3 A, B, and C show the appearance of the oil gel. The oil gels formed by the four fiber composites all have good adhesiveness ( Figure 3 A), will not flow after inverting the container ( Figure 3 B), can maintain a certain shape autonomously ( Figure 3 C). Figure 3D shows the oil holding capacity of the four oil gels. All four oil gels exhibit high oil holding capacity (>80%), and OHXO has the highest oil holding capacity, while the oil holding capacity of WHXO, PHXO, and SHXO decreases in turn.

[0044] 5. Rheological properties of oil gel The rheological properties of the oleogels were determined using a rotational rheometer (Discovery HR-2, TA Instruments, UK). Parallel steel plates with a diameter of 40 mm were used for all tests and the test gap was set to 500 μm. Amplitude sweep (strain: 0.01%–100%, frequency = 1 Hz) was used to determine the linear viscoelastic region (LVR). Frequency sweep (frequency: 0.1–100 Hz, strain: 0.1%) was used to analyze the viscoelastic properties of the samples. The amplitude ... Hz, frequency = 1 Hz) was used to determine the -1 The apparent viscosity was measured within the shear rate range. The three-interval thixotropy test (3-ITT) was used to evaluate the recovery ability of the sample. First, a low shear of 0.1 s-1 was applied to the sample, then a high shear of 10 s-1 was applied to destroy the structure, and finally a low shear of 0.1 s-1 was applied, each step lasting 60 s. The above rheological tests were all carried out at 25°C. The temperature scanning frequency was set to 1 Hz, the strain was set to 0.1%, the temperature range was 25°C-80°C, and the scanning rate was 5°C / min.

[0045] The viscoelastic properties of the oil gel were further characterized using a rheometer, such as Figure 4 As shown in the figure, in the strain sweep, frequency sweep, viscosity sweep, temperature sweep and thixotropic resilience test, the storage modulus G' of the oil gel shows a uniform change trend from high to low: OHXO>WHXO>PHXO>SHXO (shown in the figure with colors from dark to light). First, the oil gel is strain swept to determine the linear viscoelastic range. Figure 4 A, Amplitude scanning shows that the linear viscoelastic region of the sample is in the strain range of 0.01%-1%. When the strain is greater than 1%, the G' value of all oil gels begins to decrease and intersects with G", at which time the gel structure of the oil gel sample is destroyed. It is determined that the subsequent scan is performed at a strain of 0.1%.

[0046] Figure 4B shows the frequency scan of different oil gel samples. The four oil gels have G'>G'' at different frequencies, indicating that all samples exhibit solid-like elastic behavior. In the entire 0.1-100 Hz range, except for SHXO, the G' values ​​of other samples have a lower frequency dependence, which indicates that the mechanical structure of the sample gel is stronger and more stable. Among them, OHXO has the highest G' value, which may be due to its densest fiber network and its greatest strength. The fiber networks of WHXO and PHXO are relatively sparse, so their viscoelasticity is lower than that of OHXO. The higher frequency dependence of SHXO's G' value reflects the characteristics of weak cross-linking, which is closely related to the high hydrophobicity of SPIF, the long and hard fiber morphology that is not easy to cross-link, and the dispersed fiber network.

[0047] The apparent viscosity of all oleogel samples decreased with increasing shear rate ( Figure 4 C), indicating that the oil gels are all pseudoplastic fluids. The viscosity is related to the molecular weight and entanglement degree of each component in the system. OHXO has the highest apparent viscosity. Although the short and soft fibers of OVAF are not easy to entangle, their uniform distribution with hordein can produce more intermolecular interactions, which increases the viscosity of the system. WHXO and PHXO have comparable apparent viscosities. Although the fiber network and protein distribution of PHXO are sparse in terms of microstructure, when a certain dynamically changing shear force is applied to the oil gel, the long and soft self-entangled fibers may be unfolded, and certain interactions will occur with the surrounding fibers and hordein, reflecting viscous behavior. SHXO has the lowest apparent viscosity because its long and straight fibers are not easy to entangle and are unevenly distributed.

[0048] like Figure 4 D. The thixotropy test of the oil gel was carried out. The order of the apparent viscosity of the oil gel from high to low was consistent with the viscosity scan. -1 ) remains stable, and when the shear rate increases rapidly to 10 s -1 , the viscosity of all oil gel samples decreased significantly. However, when the shear rate was reduced to 0.1 s -1 When the oil gel is stirred, the apparent viscosity of the oil gel immediately recovers to a certain extent, reflecting the self-recovery of the internal structure of the oil gel. In addition, the flowing liquid oil can form a certain sliding protection effect on the gel network, reducing the further damage of the gel structure to the external mechanical force. The thixotropic resilience shows that the oil gel is suitable for complex food processing procedures.

[0049] A temperature scan was performed to understand the thermal sensitivity of the oleogel. Figure 4As shown in Figure E, as the temperature increases from 25°C to 80°C, the G' of OHXO and WHXO remains basically unchanged, showing good thermal stability, which is closely related to their dense fiber network and protein distribution. However, the G' of PHXO and SHXO shows a downward trend, indicating that they have a certain degree of thermal sensitivity, which may be due to the partial disintegration of the sparse fiber network at high temperature. During the entire test process, G'>G" of all samples, indicating that the solid-like elastic behavior is still dominant.

[0050] 6. Texture characteristics of oil gel The oil gel was subjected to a full texture analysis (TPA) using a texture analyzer (TA.XT Plus C, Stable Micro System Ltd., UK) with a cylindrical probe (P / 0.5; diameter = 10 mm). The speeds before, during, and after the measurement were set to 1.0, 1.0, and 5.0 mm / s, respectively, the test temperature was set to 25°C, the trigger force was set to 3.0 g, and the compression distance was set to 4 mm. The sample was equilibrated for 24 h before measurement, and the experiment was repeated three times.

[0051] TPA test was used to compare the mechanical properties of the four oil gels. Hardness is usually used to characterize the density of the three-dimensional network structure. As can be seen from Table 1, OHXO has the highest hardness, followed by WHXO, PHXO and SHXO, which is consistent with the order of their network density. OHXO also showed the highest viscosity, and the viscosity of WHXO and PHXO was similar, both higher than SHXO. The change trend of the viscosity of the oil gel was consistent with that of the rheological viscosity scan. There was no significant difference in elasticity among the four oil gels, which may be due to their similar slider structures. SHXO and PHXO have higher cohesion, which may be due to the loose blocks and fragments inside them, which are easy to be compressed. Chewability and gumminess are typical indicators to describe semi-solid foods, and the four oil gels have different inlet characteristics.

[0052] Table 1 Texture test of oil gel

[0053] 7. Thermal stability of oil gel The thermal behavior of the oil gel was investigated using a differential scanning calorimeter (DSC214, NETZSCH, Germany). The sample (0.0050 g) was placed in an aluminum crucible and heated from 25°C to 150°C and then cooled to 25°C at a rate of 10°C / min. The purge gas was nitrogen (40 mL / min). Soybean oil was used as a control.

[0054] The DSC curve can reflect the physical / chemical reactions of the oil gel during the heating / cooling process. Figure 5As shown in A and B, soybean oil has no endothermic or exothermic peaks in the entire heating and cooling curve, indicating that it is stable at 40-150°C. The curve of the oil gel is similar to that of soybean oil, with only slight fluctuations, which may be caused by the denaturation of internal proteins or polysaccharides. However, due to the oil wrapped around the outside of the protein / polysaccharide, its structure is protected to a certain extent, thereby greatly reducing the denaturation caused by temperature. The stability of the oil gel at daily cooking temperatures (25-150°C) reflects its great potential for application in food processing.

[0055] The embodiments described above are only some embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work shall all fall within the scope of protection of the present invention.

Claims

1. A method for preparing an oil gel based on prolamin, characterized in that: The method comprises the following steps: 1) Extraction of cereal alcohol-soluble protein: The shelled cereal kernels are crushed into powder using a high-speed grinder, and after defatting, washing with water and salt, the protein is extracted using 75% ethanol, and the extract is freeze-dried to obtain cereal alcohol-soluble protein powder; 2) Preparation of protein fiber: prepare the protein aqueous solution with deionized water, heat it under acidic conditions, and obtain the protein fiber stock solution after cooling; 3) preparing the oil gel by using the emulsion template method: dissolving the cereal alcohol-soluble protein powder prepared in step 1) in a 75% ethanol aqueous solution to prepare a cereal alcohol-soluble protein solution, then adding the cereal alcohol-soluble protein solution to the protein fiber stock solution prepared in step 2) under stirring conditions, and then adding the xanthan gum powder to the above solution; 4) adding an equal volume of vegetable oil to prepare an oil-in-water emulsion; 5) freeze-drying the oil-in-water emulsion obtained in step 4) to obtain an oil gel.

2. The method according to claim 1, characterized in that The cereals in step 1) include barley, oats, wheat, rye or corn.

3. The method according to claim 1, characterized in that The protein in step 2) includes whey protein isolate, egg white protein, soy protein isolate or pea protein isolate.

4. The method according to claim 1, characterized in that: In step 3), the concentration of the cereal alcohol-soluble protein solution is 5-15 mg / mL, and the concentration of the protein fiber solution is 5-15 mg / mL.

5. The method according to claim 1, characterized in that The volume ratio of the cereal alcohol-soluble protein solution to the protein fiber solution in step 3) is 1:1.5-3.

6. The method according to claim 1, characterized in that The final concentration of xanthan gum in step 3) is 1-4 mg / mL.

7. The method according to claim 1, characterized in that In step 4), vegetable oil including soybean oil, corn oil or peanut oil is added, and the volume of the added vegetable oil is 0.8 to 1.2 times of the solution obtained in step 3).

8. The oil gel prepared by the method according to any one of claims 1 to 7.

9. Use of the oil gel according to claim 8 in the fields of food processing, drug preparation and cosmetics.

10. The use according to claim 9, characterized in that: The applications include as food ingredients or processing aids, as carrier matrix, as a substitute for trans fatty acids, as a drug carrier, as a nutritional supplement, and as a matrix for sunscreens and / or skin care products.

Citation Information

Patent Citations

  • Zein fat substitutes based on vacuum distillation as well as preparation and application of zein fat substitutes

    CN105054077A

  • Zein oil-bearing gel and preparation method thereof

    CN108200969A

  • Method for preparing oil gel from protein gel

    CN114190443A

  • Method for preparing cyperus esculentus oil oleogel from edible polymer

    CN115708531A

  • Antarctic krill oil gel material as well as preparation and application thereof

    CN115736254A

Cited By

  • High-stability structural fat suitable for healthy fat replacement as well as preparation method and application of high-stability structural fat

    CN120713173A